Prognostic importance of lymph node count and ratio in rectal cancer after neoadjuvant chemoradiotherapy: Results from a cross‐sectional study. Issue 3 (14th May 2021) - Detering, Robin; Meyer, Vincent M.; Borstlap, Wernard A.A.; Beets‐Tan, Regina G.H.; Marijnen, Corrie A.M.; Hompes, Roel; Tanis, Pieter J.; van Westreenen, Henderik L.; ,
Abstract: Background: The aim of this study was to determine the prognostic value of lymph node count (LNC) and lymph node ratio (LNR) in rectal cancer after neoadjuvant chemoradiotherapy (CRT). Methods: Patients who underwent neoadjuvant CRT and total mesorectal excision (TME) for Stage I–III rectal cancer were selected from a cross‐sectional study including 71 Dutch centres. Primary outcome parameters were disease‐free survival (DFS) and overall survival (OS). Prognostic significance of LNC and LNR (cut‐off values 0.15, 0.20, 0.30) was tested for different (sub)groups. Results: From 2095 registered patients, 458 were included, of which 240 patients with LNC < 12 and 218 patients with LNC ≥ 12. LNC was not significantly associated with DFS ( p = 0.35) and OS ( p = 0.59). In univariable analysis, LNR was significantly associated with DFS and OS in the whole cohort and LNC subgroups, but not in multivariable analysis. Conclusions: LNC was not associated with long‐term oncological outcome in rectal cancer patients treated with CRT, nor was LNR when corrected for N‐stage. However, LNR might be used to identify subgroups of node‐positive patients with a favourable outcome. Highlights: Lymph node count < 12 has no impact on survival after neo‐adjuvant chemoradiotherapy for rectal carcinoma. Lymph node count and ratio are not of additional value besides N‐stage in rectal cancer patients who underwent neoadjuvant chemoradiotherapy. Lymph node ratio could identify subgroups of node‐positive patients with a favourable outcome.